Reduced Mobility or the Bow and Arrow? Another Look at "Expedient" Technologies and Sedentism. Issue 2 (20th April 2010) - Railey, Jim A.
Abstract : Parry and Kelly (1987) argued for a causal link between expedient technologies and sedentism, and their explanation has widely influenced lithic analysts. There are some problems with their explanation, however, including disconnects in the reported timing of the shifts to expedient technologies, agricultural intensification, and sedentism. On the other hand, across much of North America the transition to an expedient technology appears to correlate more closely to the arrival of the bow and arrow. This is supported by data from a large excavation project in southern New Mexico, which shows that indicators of the shift to an expedient technology cannot be attributed to reduced mobility or any observable changes in subsistence practices, but do appear to correlate temporally with the appearance of arrow points.